Physical and geographical features of the Fergana Valley - Zhabbarov Azam Mashrabovich (International Journal on Orange Technologies, 2021)
This article highlights the physical and geographical features of the Fergana Valley: the physical, geographical and political border, water resources, climate, seasons. The concept of the Fergana term: the history of its research, about memorable places in the valley, mountains and deserts, about soils and the development of virgin lands, environmental protection